Study on correlation between property of coronary artery lesion and degree of coronary artery stenosis of elderly patients with coronary heart disease - Wang, Chao (Pak J Med Sci, 2019)
OBJECTIVE: To discuss the influence of coronary artery lesion of elderly patients with coronary heart disease (CHD) on left ventricular remodeling. METHODS: Retrospective selection method was used to choose 80 elderly CHD patients who received coronary angiogram examination in Baoding First Central Hospital from January 2014 to February 2018 as the objects of study. According to coronary artery lesion, the patients were classified into single vessel lesion group (single vessel group) and multi-vessel lesion group (multi-vessel group, the number of lesion vessels≧2). Single vessel group included 60 patients, and multi-vessel group includes 20 patients. Intravascular unltrasound was applied to record coronary plaque property of all patients and transthoracic echocardiography was used to record left ventricular remodeling. Later correlation analysis was carried out. RESULTS: The proportion of calcified plaque and mixed plaque was higher than that of single vessel group, and the differences had statistical significance (P<0.05). Left ventricular end diastolic volume (LVEDV) and left ventricular end-systolic volume (LVESV) of multi-vessel group were higher than that of single vessel group, while left ventricular ejection fraction (LVEF) was lower than that of single vessel group. The differences had statistical significance (P<0.05). Linear correlation analysis showed coronary artery lesion was positively correlated with LVEF and calcified plaque (r=0.287, 0.371, P<0.05). Multiple linear regression analysis showed LVEF, calcified plaque and LDL-C were independent risk factors of multi-vessel coronary artery lesion of old CHD patients (P<0.05). CONCLUSION: The number of coronary artery lesions is significantly correlated with left ventricular remodeling, and can increase the proportion of calcified plaque and mixed plaque, thus leading to left ventricular remodeling abnormity.